Associations between air pollution and socioeconomic characteristics, ethnicity and age profile of neighbourhoods in England and the Netherlands. (March 2015) - Fecht, Daniela; Fischer, Paul; Fortunato, Léa; Hoek, Gerard; de Hoogh, Kees; Marra, Marten; Kruize, Hanneke; Vienneau, Danielle; Beelen, Rob; Hansell, Anna
Abstract: Air pollution levels are generally believed to be higher in deprived areas but associations are complex especially between sensitive population subgroups. We explore air pollution inequalities at national, regional and city level in England and the Netherlands comparing particulate matter (PM10 ) and nitrogen dioxide (NO2 ) concentrations and publicly available population characteristics (deprivation, ethnicity, proportion of children and elderly). We saw higher concentrations in the most deprived 20% of neighbourhoods in England (1.5 μg/m 3 higher PM10 and 4.4 μg/m 3 NO2 ). Concentrations in both countries were higher in neighbourhoods with >20% non-White (England: 3.0 μg/m 3 higher PM10 and 10.1 μg/m 3 NO2 ; the Netherlands: 1.1 μg/m 3 higher PM10 and 4.5 μg/m 3 NO2 ) after adjustment for urbanisation and other variables. Associations for some areas differed from the national results. Air pollution inequalities were mainly an urban problem suggesting measures to reduce environmental air pollution inequality should include a focus on city transport. Highlights: Air pollution inequalities are believed to vary between subpopulations. We explore this across two European countries at different geographical levels. We found that air pollution inequalities are largely an urban problem. Ethnically diverse neighbourhoods have the highest air pollution levels. Associations vary across two countries that might be thought to be quite similar. Abstract : Air pollution inequalities are largely an urban problem and associations with deprivation and ethnicity vary even across two European countries that might be thought to be quite similar.